2009
DOI: 10.1016/j.enpol.2008.07.029
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the Norwegian carbon dioxide, capture and storage innovation system

Abstract: In order to take up Norway's twin challenge of reducing CO 2 emissions, while meeting its growing energy demand with domestic resources, the deployment of carbon capture and storage (CCS) plays an important role in Norwegian energy policies. This study uses the Functions of Innovation Systems approach to identify key policy issues that need to be addressed in order to prolong Norway's international leadership position in the development of CCS. The analysis shows that Norway has been successful in building an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 45 publications
1
32
0
1
Order By: Relevance
“…This TIS framework with its discrete functions has been applied to multiple technologies in various contexts with a goal of identifying leverage points for enhancing or accelerating the innovation process, including one particularly relevant empirical analysis of CCS development in Norway (Alphen et al, 2009). While our approach does not apply these same categories of functional analysis, we focus on core elements that cross-cut the seven functions.…”
Section: Shifts In Energy Systems and Energy Systems Researchmentioning
confidence: 99%
“…This TIS framework with its discrete functions has been applied to multiple technologies in various contexts with a goal of identifying leverage points for enhancing or accelerating the innovation process, including one particularly relevant empirical analysis of CCS development in Norway (Alphen et al, 2009). While our approach does not apply these same categories of functional analysis, we focus on core elements that cross-cut the seven functions.…”
Section: Shifts In Energy Systems and Energy Systems Researchmentioning
confidence: 99%
“…The functions of the TIS approach has been applied to CCS previously by Van Alphen et al (2008), showing that knowledge development and diffusion are generally the best-developed functions of the CCS TIS, with market formation being the weakest. Moreover, Van Alphen et al (2009) showed that Norway has a strong CCS TIS as compared to, for example, the US and Australia. Zawadski (2009) compared the CCS TIS with those of wind and fuel cell technologies in Canada and found that CCS was seen to perform better with regard to funding.…”
Section: Expectations and Interestsmentioning
confidence: 97%
“…Hydroelectric power generation is one example, another is the focus on oil and gas since the 1970's (Tamnes, 1997). Finally, the Norwegian energy-political response to the climate issue has been massive efforts to develop carbon capture and storage technology (CCS) (van Alphen, van Ruijven, Kasa, Hekkert, & Turkenburg, 2009). It has been suggested that in Norway, CCS has found a politically harmonizing role, as a 'necessary compromise' between environmental and industrial interests.…”
Section: The Swedish and Norwegian Energy Regimesmentioning
confidence: 99%